A Note on Hallucinatory Film - Harris, Mark (Hungarian Journal of English and American Studies, 2021)
Comparisons between hallucinatory films of the 1960s and 2000s show a conversion of the earlier utopian signifiers from benign fields of intoxicating color that celebrate and induce psychic bliss, into high-definition alarm bells for a world imploding from accelerated hyperconsumption. Paranoid, conspiracy-driven 70s commercial cinema, which appropriates editing techniques from earlier experimental films, marks a threshold of disenchantment. The entropic model of 60s hallucinatory works by Stan Brakhage, Carolee Schneemann, and others, where film material and abstract imagery are modified analagous to the intensification of bodily pleasures, is digitally exacerbated in high-definition videos of Heather Phillipson, Ed Atkins, and Benedict Drew as if collapsing under environmental and psychic degradation. This later work maximizes hallucinatory HD properties through relentlessly overlaying imagery of interpenetrating, deflating, and exploding bodies that are avatars of overindulgence, the nightmarish uncanny descendants of 60s utopian intoxications. (MH)